In vitro interleukin 4 and interferon-gamma production by mononuclear cells from atopic dermatitis patients - Serge Well; Friedhelm Diel (Mediators of Inflammation)
In order to elucidate further the possible role of specific cytokines in the pathogenesis of atopic dermatitis (AD) the in vitro production of interleukin 4 (IL-4) and interferon-gamma (IFN-γ) in patients with severe atopic dermatitis (n = 4) was compared with that in a group of non-atopic healthy controls. Overall IL-4 production by PHA- and PWM-driven PBMNCs was increased in controls during the first 48 h in culture. Addition of interleukin 2 (IL-2) into parallel cultures generated an insignificant (p > 0.05) increase in IL-4 production in AD patients compared with that from controls. IFN-γ production by PWM-stimulated PBMNCs was markedly decreased in AD patients compared with controls (p < 0.01). Addition of IL-2 (250 U/ml) to parallel cultures failed to restore IFN-γ production in AD patients. Finally, no IL-4 or IFN-γ activity could be detected in any of the sera. In conclusion, the data suggest a possible dysregulation of cytokine production in at least a subgroup of AD patients, with an impaired capacity to secrete IFN-γ, but a partially intact IL-4 generating capacity.